(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
According to modern text joint is a place where two or more bones are articulates with each other. Aacharya Sushruta has quoted that although there are numerous Sandhi in our body which cannot be counted so only Asthi Sandhi should be considered while enumerating Sandhi. Total two hundred and ten Sandhi are present in human body. Every bone is unite by joints and covered by muscles and gets blood supply by different Sira and Dhamani. These bones unite to form Asthi Sandhi. In Ayurveda the main Sthana of Kapha Dosha is all joints in human body. Janu Sandhi (knee) is the largest and most complex synovial joint of the body and is of great importance because it plays great role in movements like walking and stability, including maintenance of the erect posture and the transmission of the body weight. Sandhi can be taken as union of two or more bone in Ayurvedic Samhitas the description of anatomy of Sandhi in detail is not found. It is observed that the incidence of joints disorders is increasing day by day. It is burning problem for families and society. A thorough knowledge of the structures and functions of the joint is required to diagnose and treat the disease of joints.